Epigenetic Regulations in Neural Stem Cells and Neurological Diseases - Hang Zhou; Bin Wang; Hao Sun; Xingshun Xu; Yongxiang Wang (Stem Cells International)
Among the regulatory mechanisms of the renewal and differentiation of neural stem cells, recent evidences support that epigenetic modifications such as DNA methylation, histone modification, and noncoding RNAs play critical roles in the regulation on the proliferation and differentiation of neural stem cells. In this review, we discussed recent advances of DNA modifications on the regulative mechanisms of neural stem cells. Among these epigenetic modifications, DNA 5-hydroxymethylcytosine (5hmC) modification is emerging as an important modulator on the proliferation and differentiation of neural stem cells. At the same time, Ten-eleven translocation (Tet) methylcytosine dioxygenases, the rate-limiting enzyme for the 5-hydroxymethylation reaction from 5-methylcytosine to 5-hydroxymethylcytosine, play a critical role in the tumorigenesis and the proliferation and differentiation of stem cells. The functions of 5hmC and TET proteins on neural stem cells and their roles in neurological diseases are discussed.